2019
DOI: 10.1002/ar.24099
|View full text |Cite
|
Sign up to set email alerts
|

Filling in Gaps in the Ceratopsid Histologic Database: Histology of Two Basal Centrosaurines and an Assessment of the Utility of Rib Histology in the Ceratopsidae

Abstract: Bone histology grants substantial insight into the growth and biology of fossil vertebrates. Many of the major non‐avian dinosaurian clades have been extensively sampled for bone histologic data allowing reconstruction of their growth as well as the assessment of the evolution of growth changes along phylogenies. However, horned ceratopsians are poorly represented in paleohistologic studies. Further, the ceratopsian taxa that have been examined are unevenly sampled phylogenetically with very basal forms and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In the pterosaur Pteranodon no ‘immature’ bone grain was found in individuals that possessed postcranial co‐ossifications or fully ossified epiphyses (Bennett, 1993). This is despite evidence that periodic interruption of growth occurred during ontogeny in both centrosaurines (Levitt, 2013; Hedrick et al ., 2020) and in Pteranodon and other pterodactyloid pterosaurs (Sayão, 2003; Chinsamy, Codorniú & Chiappe, 2008; Chinsamy et al ., 2009; Bennett, 2018). There is, therefore, much work to be done to determine how long bone surface textures relate to histology and other metrics of maturity in different clades of extinct taxa, many of which grow unlike any reptiles alive today.…”
Section: Methods Of Assessing Maturitymentioning
confidence: 99%
“…In the pterosaur Pteranodon no ‘immature’ bone grain was found in individuals that possessed postcranial co‐ossifications or fully ossified epiphyses (Bennett, 1993). This is despite evidence that periodic interruption of growth occurred during ontogeny in both centrosaurines (Levitt, 2013; Hedrick et al ., 2020) and in Pteranodon and other pterodactyloid pterosaurs (Sayão, 2003; Chinsamy, Codorniú & Chiappe, 2008; Chinsamy et al ., 2009; Bennett, 2018). There is, therefore, much work to be done to determine how long bone surface textures relate to histology and other metrics of maturity in different clades of extinct taxa, many of which grow unlike any reptiles alive today.…”
Section: Methods Of Assessing Maturitymentioning
confidence: 99%
“…This shows that the mammalian (endothermic) histological growth is not dependent on climatic conditions but rather by endogenous constraints. Hedrick et al (2020) suggested an initial climate-induced gradient in growth patterns for ceratopsian dinosaurs, but additional sampling of closely-related taxa from geographically similar localities showed marked differences in histology, thus these patterns were most likely phylogenetically induced.…”
Section: Growth Marks and Environmental Influencementioning
confidence: 99%
“…His contributions to understanding the world of dinosaurs—from his paleontological findings, scholarly writings, museum exhibit creations, and birthing of superb progeny—have made him stand out in the world of dinosaur science. Indeed, Peter has given much to our own journal, being a frequent contributor (e.g., Dodson, 2003, 2009, 2020; Hedrick et al, 2020, 2022; Schachner et al, 2009, 2011; Tumanova et al, 2023), and Guest Editing two of the most popular Special Issues in our history, “Unearthing the Anatomy of Dinosaurs: New Insights into their Functional Morphology and Paleobiology” (Dodson, 2009; Laitman, 2009; Laitman & Albertine, 2009) and “The Hidden World of Dinosaurs” (Hedrick & Dodson, 2020; Laitman & Albertine, 2020; Figure 2). The 2009 Special Issue, our first on dinosaurs, was so much in demand that our Publisher, Wiley, had to print additional copies for individual sale (Dodson Dinos make money, at least for Wiley!…”
Section: Figurementioning
confidence: 99%